Keterlibatan Stakeholder dalam Penanganan Stunting di Gampong Lam Ujong Aceh Besar - Jannah, Rozatul; Rizqil A, Muhammad; Hanunawati; Khairudiza; Warid, Khablil; Khairul Ajyal, Muhammad (Program Studi Ilmu Administrasi Negara Bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This study aims to explore the involvement of stakeholders in handling stunting in Gampong Lam Ujong, Aceh Besar. Stunting is a chronic health problem that affects children's growth due to long-term malnutrition. This research uses descriptive qualitative methods with data collection techniques in the form of interviews, observation, and documentation. The focus of the research is the role of stakeholders, such as keuchik, posyandu cadres, village midwives, and the community in the implementation of the stunting handling program. The results showed that collaboration between various stakeholders has contributed significantly to reducing stunting rates in Gampong Lam Ujong. The Supplementary Feeding Program (PMT), supporting facilities, and active involvement of posyandu and the community are key success factors. Strong leadership, clear procedural mechanisms, and well-allocated resources also support the effectiveness of the program. However, this study also found several challenges, such as budget constraints, low parental participation in supporting children's nutritional intake, and the need for improved program monitoring. This study recommends strengthening the capacity of health cadres, improving nutrition education, and more intensive collaboration with related parties to ensure program sustainability.